Holographic portraits: from reality to artistic creation - Oliveira, Rosa M. (2004)
The different concepts of artistic holography have contributed to the development of new ways of understanding reality. Holography makes it possible to express different visions of the recorded subject. In this work, from a primary portrait recorded with a pulsed ruby laser, a new kind of portrait will be created. The extremely realistic image of the master hologram will be transformed in a secondary expressionist multicoloured hologram. Using an emulsion manipulating technique before exposure, the portrait is changed, in order to achieve new visions of reality.